Intermittent chemoprophylaxis for Pneumocystis carinii pneumonia. - Hughes, W T (1983)
An intermittent regimen of trimethoprim-sulfamethoxazole was tested in the corticosteroid-treated rat model to learn whether or not administration for 3 consecutive days a week would provide prophylaxis equal to continuous daily doses. Although all of the untreated control animals acquired Pneumocystis carinii pneumonia, none of the animals given either continuous or intermittent trimethoprim-sulfamethoxazole became infected.